The TCR and LCK: foundations for T-cell activation and therapeutic innovation - Woessner, Nadine M.; Uleri, Valeria; Stepanek, Ondrej; Minguet, Susana (Frontiers in Immunology, 2026)
The T cell receptor (TCR)-CD3 complex is crucial to adaptive immunity, driving antigen recognition and intracellular signaling cascades. CD3 subunits harbor key cytoplasmic motifs that recruit signaling proteins like LCK. While distal αβ TCR signaling is well-understood, gaps persist in our understanding of proximal signaling, particularly the roles of free versus co-receptor CD4 or CD8-associated LCK and their impact on antigen sensitivity and activation thresholds. In contrast to αβ T cells, γδ T cells recognize diverse antigens, often independently of MHC or MHC-like molecules. Despite their shared CD3 signaling components, the proximal signaling mechanisms of γδ T cells remain poorly characterized, raising important questions about their activation pathways and kinase dependencies. Addressing these gaps is essential to unlock the unique therapeutic potential of γδ T cells in cancer immunotherapy. Recent advances in engineered T-cell therapies demonstrate how proximal TCR signaling can be leveraged for therapeutic innovation. Chimeric antigen receptor (CAR) and chimeric-TCR designs that incorporate specific CD3 signaling motifs have shown improved anti-tumor activity, reduced exhaustion, and enhanced persistence, reflecting a shift beyond traditional ζ chain-dominated designs. In parallel, emerging small-molecule modulators targeting early TCR events offer new strategies to tune pathogenic T-cell responses in autoimmunity or to reset exhausted CAR T cells. This review explores the critical roles of CD3 motifs and LCK in TCR activation, with a focus on the underexplored γδ T cells. We also discuss how these insights could drive next-generation cancer immunotherapies and novel treatments for autoimmune diseases and immunopathologies.